Coexistence of Emphysematous Pyelonephritis and Cystitis in a Patient with COVID-19 Complicated with Spontaneous Pneumomediastinum - Ibrahim Boukhannous; Anouar El Moudane; Mehdi Chennoufi; Mohamed Mokhtari; Abdelghani Ouraghi; Hamza Mimouni; Ali Barki (Case Reports in Infectious Diseases)
We report the first case of a 52-year-old nondiabetic male admitted for management of uremic syndrome associated with emphysematous pyelonephritis (EPN), renal and perinephric abscess, and emphysematous cystitis (EC) on a single functional kidney with a large abundance of spontaneous pneumomediastinum (SP) complicating a SARS-CoV-2 pneumonia. The patient has benefited from several dialysis sessions, intravenous antibiotics, and percutaneous drainage. His clinical course was complicated by acute respiratory distress syndrome, and unfortunately, he died nine days following admission.